African Industrial Design Practice Perspectives on Ubuntu Philosophy - Moalosi, Richie; Rapitsenyane, Yaone (Taylor & Francis, 2024)
Product design,Industrial design,African studies,Afrika,Africa,Sustainability,Ethical design,3D printing,Ubuntu Philosophy,Decolonial Lens,NPD Process,Micro Enterprises,Industrial Design,Co-creation Process,Business Model Canvas,Afrikan Culture,Adinkra Symbols,Business Case,Traditional Cultural Expressions,Digital Manufacturing,AM,Sustainable Product Service System,Design Education,SME,Superimposed,High Fidelity Prototype,Low Fidelity Prototypes,Held,Industrial Design Profession,SME Business,Defensive Strategy,Design Sketching,Manual Sketching